PENGARUH KEPEMILIKAN MANAJERIAL DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN DI INDONESIA - CAROLIN , GISELA ANINDITA; MARIA, MARIA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The purpose of this study aims to offer empirical evidence concerning managerial ownershipand other factors on firm value companies in Indonesia. Managerial ownership consists of managers,directors, or commissioners who are actively involved in company decision making. The research samplewas determined using a purposive sampling approach and analyzed through the multiple regressionmethod resulted 74 non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2021to 2023 with 222 data that passed the research criteria. The results of this study show that independent variables consisting of profitability, capital structure and liquidity have an influence on firm value. While other variables such as company size, company growth, dividend policy, and managerial ownership have no influence on firm value